Karakteristik Karkas, Sifat Fisik dan Kimia Daging Rusa Sambar (Rusa unicolor) - Bram Brahmantyo; Wirdateti Wirdateti; Gono Semiadi (Buletin Plasma Nutfah, 2013)
Venison isknown as qualified meat because of its softness and fineness offiber, protein and iron are very high, as well as fat, cholesteroland energy are low. Today, consumers are likely to eat meatwith low fat. Venison will be able to meet the needs of themarket. This study aimed to evaluate carcass production,physical and chemical properties of venison of captive Sambardeer (Rusa unicolor). Three heads of adult Sambar deer fromthe Regional Technical Implementation Unit Breeding andArtificial Insemination Center, East Kalimantan were used.Deers were fasted for 24 hours and slaughter with cuttingjugular veins, esophagus and throat. Observations were madeon the carcass, commercial cuts, physical properties andchemical properties of venison. Averages of carcasspercentage, meat to bone ratio, and major commercial cutswere 50.17, 3.35, and 56.01%, respectively. The physicalproperties of the venison was very good and was notinfluenced by commercial cuts. Loin were higher on fatcontent (0.65+0.18 g/100 g) and cholesterol (48.33+11.59mg/kg) than the fillet and leg cuts.